Rational Expectations in Price Setting. Tests Based on Norwegian Export Prices - Ingvild Svendsen (Statistics Norway, Research Department, 1998)
This paper uses imperfect competition as a basis for modelling the export price for an aggregated commodity produced by the Norwegian private mainland economy. The long run solution is analysed using a cointegration technique. The dynamics are modelled according to two different approaches; a backward looking error correction model and a forward looking model where rational expectations are assumed. The dynamic structure of the forward looking model is derived from a linear quadratic adjustment cost function under rational expectations, but the empirical results do not support this specification. We cannot reject super-exogeneity to be present in the backward looking error correction model. The empirical evidence are thus not consistent with rational expectations.
Keywords: C51; C52; D84; E31; 330; Export price; Imperfect competition; LQAC models; ECM; Cointegration; Rational expectation; Super exogeneity